Exogenous Jaagsiekte sheep retrovirus (JSRV) Inner Mongolia strain: whole-genome characterization and viral particle packaging - Zhang, Pei; Wang, Yu; Duan, Xujie; Chen, Sixu; Du, Xiaoyue; Bao, Anyu; Ma, XinQi; Zhang, Yufei; Liu, Shuying (Frontiers in Veterinary Science, 2025)
IntroductionOvine pulmonary adenocarcinoma (OPA) is a contagious lung tumor caused by the exogenous Jaagsiekte sheep retrovirus (exJSRV). Analysing the genome of the pathogen is crucial for developing OPA prevention and control measures. Due to the absence of exogenous genomic JSRV-related information in Inner Mongolia, we aimed to establish a specific technique for exJSRV genomic amplification.MethodsTarget virions were purified using U3 hn-PCR (hemi-nested PCR) combined with density gradient centrifugation. Specific reverse transcription primers were designed using the low-identity region of the internal and external genome, combined with long fragment PCR and 3′RACE technology, and the full-length genome of exogenous JSRV from Inner Mongolia was successfully obtained.ResultsExogenous molecular characteristics were found in the long terminal repeat(LTR)-U3 region, gag-variable region 1/2(VR1/VR2) and env-VR3, and was 98.8% identical to the Chinese JSRV-C1, which was significantly higher than that of foreign isolates (93.05–95.84%) and enogenous Jaagsiekte sheep retrovirus (enJSRV) (88.73–92.26%). Phylogenetic analysis showed that NMJS12 and exogenous JSRV-C1 were located in the same evolutionary clade. Accordingly, the whole genome eukaryotic expression plasmid was successfully constructed and viral particle packaging was achieved in 293T cells.ConclusionAltogether, this study represents the first elucidation of the complete genome of exogenous JSRV in Inner Mongolia, China and provides a critical material foundation for antiviral target screening and research on OPA pathogenesis.